Evaluasi Implementasi Kebijakan Standar Pelayanan Minimal Bidang Kesehatan di Kabupaten Gunungkidul - KHOZIN, MOHAMMAD (Jurnal Studi Pemerintahan, 2010)
Minimum service standard policy applied since 2002 are based on the Minimum Service Standard (SPM) arranged in circular Minister of Home Affairs No. 100/756/OTDA/2002, then set up further in Government Regulation No. 65 2005 edge various obstacles both at internal level bureaucracy nor the external environment. This research tries to answer how far the implementation of the policy of Minimum Service Standards could improve the quality of health service?. The public service is an activity that is performed by a person or a group of people with a materially factors through the system, specific procedures and methods in order to attempt to satisfy the interests of others in accordance with his authority. The research method used is a qualitative method by combining data analysis of primarydan data secondary. Standard service for a minimum of Gunungkidul Regency field can be accomplished with either. This can be seen from a comparison of the data from the indicator one year sections that have been compiled. But of the many indicators of the performance of service sections that have been set, still there are some indicators that are not obvious targeting.